2013
DOI: 10.1016/j.healthplace.2013.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic inequalities in injury mortality in small areas of 15 European cities

Abstract: This study analysed socioeconomic inequalities in mortality due to injuries in small areas of 15 European cities, by sex, at the beginning of this century. A cross-sectional ecological study with units of analysis being small areas within 15 European cities was conducted. Relative risks of injury mortality associated with the socioeconomic deprivation index were estimated using hierarchical Bayesian model. The number of small areas varies from 17 in Bratislava to 2666 in Turin. The median population per small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
4
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 33 publications
6
43
4
2
Order By: Relevance
“…Many of the deaths from external causes are due to traffic accidents, and it may be that, in Spain, residents in areas with worse socioeconomic context have less exposure to that risk. The results of the present study are consistent with those of an ecologic study of inequalities in mortality from external causes in various European cities, which found that the cities of Madrid and Barcelona had the lowest inequality in mortality from external causes (Gotsens et al, 2013).…”
Section: Comparison With Other Studies and Possible Explanationssupporting
confidence: 91%
“…Many of the deaths from external causes are due to traffic accidents, and it may be that, in Spain, residents in areas with worse socioeconomic context have less exposure to that risk. The results of the present study are consistent with those of an ecologic study of inequalities in mortality from external causes in various European cities, which found that the cities of Madrid and Barcelona had the lowest inequality in mortality from external causes (Gotsens et al, 2013).…”
Section: Comparison With Other Studies and Possible Explanationssupporting
confidence: 91%
“…Likewise, a study in Barcelona13 reported the association with neighbourhood unemployment and fall mortality rate, after adjusting for individual level SEP. In contrast, studies in European cities12 and Canada11 reported that there were no associations between area level deprivation and mortality from fall injuries. In South Korea, senior citizens with a lower household income were reportedly more susceptible to fall related fatalities due to the increased risks from their residential conditions, with hazards such as steep street slopes, poorly designed stairs and slippery bathroom tiles 30.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies examining this association showed mixed results. A study of European cities with a cross sectional ecological design12 reported that deprived small areas had greater mortality risks of transport injuries in men but not in women. Meanwhile, the most deprived areas, independent of individual level SEP, had a significantly greater mortality from traffic accidents compared with the least deprived areas in the USA10 and Canada11 but not in Barcelona 13.…”
Section: Discussionmentioning
confidence: 99%
“…Our data also showed that the socioeconomic inequalities in suicide were heightened in males compared to females. Similarly, a recent study found that socioeconomic inequalities in suicide were more noticeable in men than in women in European cities (Gotsens et al, 2013). Studies investigating associations between suicide rates and deprivation in London also showed stronger association in young and middleaged men than other sex/age groups (Congdon, 1996b;Rezaeian et al, 2007).…”
Section: Inequalities In Suicidementioning
confidence: 86%
“…National suicide rates range between close to zero and above 30 per 100,000 globally (Varnik, 2012). Within individual countries the incidence of suicide could reveal distinct national geographic patterns (Middleton et al, 2008) or even vary substantially within cities (Gotsens et al, 2013).…”
Section: Introductionmentioning
confidence: 99%